Determination of the Effective Factors in Predicting ART Outcome in Women With RIF (Recurrent Infertility Failure) - Shaghayegh Khatami; Farahnazsadat Ahmadi; Elham Shirali; Sina Mohajernoei; Roghaye Gharae; Mahboubeh Tajaldini; Valiollah Alishahi (Acta Medica Iranica)
Recurrent implantation failure (RIF) remains a significant challenge in assisted reproductive technology (ART), affecting a substantial proportion of patients undergoing treatment. While advancements in ART have improved outcomes, the multifactorial nature of RIF complicates its management. This study aims to evaluate the factors influencing RIF and identify potential predictors of ART success in affected patients. A retrospective analysis was conducted on 123 women with at least two failed implantation attempts. Demographic, clinical, and laboratory data were collected, including age, body mass index (BMI), uterine abnormalities, sperm quality, and embryo formation. Statistical analyses were performed to evaluate the relationships between these variables and ART outcomes. Most participants (62.6%) were under 35 years of age, and BMI was significantly associated with the number of embryos formed (P=0.037). Among the participants, 69.91% had bilaterally patent fallopian tubes, while uterine abnormalities were linked to reduced implantation success. Sperm motility showed a significant correlation with embryo formation (P<0.05), whereas sperm count, and morphology were not statistically significant predictors. Despite comprehensive evaluations, only 1.6% of patients achieved live births, underscoring the complexity of RIF. This study highlights the critical roles of maternal age, BMI, uterine health, and sperm motility in influencing ART outcomes. Addressing modifiable factors such as BMI and uterine abnormalities and optimizing sperm quality may enhance the likelihood of successful implantation. Further research is needed to explore additional predictors and develop personalized treatment strategies for patients with RIF.